Initial solid tumor testing (Stage 1) of AZD1480, an inhibitor of Janus kinases 1 and 2 by the pediatric preclinical testing program. Issue 11 (17th August 2014) - Houghton, Peter J.; Kurmasheva, Raushan T.; Lyalin, Dmitry; Maris, John M.; Kolb, E. Anders; Gorlick, Richard; Reynolds, C. Patrick; Kang, Min H.; Keir, Stephen T.; Wu, Jianrong; Smith, Malcolm A.
<x xml:space="preserve">Abstract</x> Background AZD1480 is an ATP competitive inhibitor of Janus kinases 1 and 2 (JAK1, 2) that has been shown to inhibit the growth of solid tumor models. This agent was selected for testing the putative role of JAK/STAT signaling in the standard PPTP solid tumor models. Procedures AZD1480 was tested against the PPTP in vitro cell line panel at concentrations from 1.0 nM to 10 μM and against the PPTP in vivo solid tumor xenograft panels at (60 mg/kg once daily (SID) × 5) for three consecutive weeks. Additional studies evaluated 5 to 20 mg/kg BID × 5 with SID dosing at 7–30 mg/kg at weekends for three consecutive weeks. Results In vitro the median relative IC50 (rIC50) for the PPTP cell lines was 1.5 µM, with a range from 0.3 µM to 5.9 µM. The two cell lines with rIC50 values of 0.3 µM both had ALK activating genomic alterations. AZD1480 demonstrated statistically significant differences (P < 0.05) in EFS distribution compared to control in 89% of the solid tumor xenografts. AZD1480 induced intermediate (EFS T/C > 2) or high‐level growth inhibition in 15 of 30 (50%) solid tumor xenografts. Tumor regressions were observed in three of six Wilms tumor models at doses that induced inhibition of Stat3(Y705) phosphorylation. Conclusions AZD1480 demonstrated significant tumor growth inhibition against most PPTP solid tumor xenografts, similar to that observed for antiangiogenic agents tested by the PPTP. Tumor regressing activity was noted for Wilms tumor xenografts. Pediatr Blood Cancer 2014;61:1972–1979. © 2014 Wiley Periodicals, Inc.